Re-defining the traditional neighborhood areas in the historical city center- Saray Sulaimani as a case study - Rasul, Hoshyar Q.; Muhammed, Hussein D. (Sulaimani Journal for Engineering Sciences, 2019)
It is widely accepted, that historic urban quarters are coherent entities, which are clearly identified by their traditional character and architectural values and meanings. These areas have been described as critical areas in the city, because they hold and kept in the same time the identity of the city, and been more decayed day by day due to obsolescence phenomenon which faced these areas continuously. In this regard, Sulaimania city center showed many kinds of developments, which are totally not exceeds the individual buildings oriented. The way that these individual buildings had become as a landmark of the city, because of its richness in holding many historical, architectural, heritage values. The last was the rehabilitation of Sulaimania - Saray building. Examination of successful examples of revitalization projects for historic urban quarters in different cities shows that, aside from the application of effective organizational, legal, fiscal, financial tools, correct identification of the contextual attributes during the analytical stage plays a key role in determining the appropriate strategic approach to revitalization. From this point of view, the problem research derived as the lack of contextualism perspective in revitalization projects in historical traditional areas in the city center leads to what known as building based instead of area-based protection. The study tries to achieve objectives underlying as necessity of treating these areas as one integrative unit which are participating in drawing the context of urban scene, and any effort to separate building from its context leads to fragment the urban tissue specially in the urban center, and of course this whole view can pave the road to re-define these decayed areas in the way described as more widely and sustainable method.
Keywords: Historical urban quarter; traditional neighborhood; Redefining; contextualism; identity of place